Sens zatrzymany w numinosum - Ciesielski, Remigiusz (Polskie Towarzystwo Religioznawcze, 2010)
Remigiusz T. Ciesielski – A MEANING STUCK IN A NUMINOSUM In this article I put special attention to problems of interpretation of the results of sociological research on the experience of a religious nature. Public religiosity is correlated with changes of political or economic nature. It is associated with experience similar to the category of the practice numinosum as R. Otto understands them. A description of this experience in contemporary culture, both in literature and in social studies, leads to confusion of interpreting the behavior of this type. Article based on the reflections presented by: G. Simmel, R. Guardini and J. Ratzinger.